Co-Occurrence of NDM-5 and RmtB in a Clinical Isolate of Escherichia coli Belonging to CC354 in Latin America - Costa, Agustina (2021)
New Delhi metallo-β-lactamase (NDM)-producing isolates are usually resistant to most β-lactams and other antibiotics as a result of the coexistence of several resistance markers, and they cause a variety of infections associated to high mortality rates. Although NDM-1 is the most prevalent one, other variants are increasing their frequency worldwide. In this study we describe the first clinical isolate of NDM-5- and RmtB-producing Escherichia coli in Latin America. E. coli (Ec265) was recovered from a urine sample of a female outpatient. Phenotypical and genotypical characterization of resistance markers and conjugation assays were performed. Genetic analysis of Ec265 was achieved by whole genome sequencing. Ec265 belonging to ST9693 (CC354), displayed resistance to most β-lactams (including carbapenems), aminoglycosides (gentamicin and amikacin), and quinolones. Several resistance genes were found, including blaNDM-5 and rmtB, located on a conjugative plasmid. blaNDM-5 genetic context is similar to others found around the world. Co-transfer of multiple antimicrobial resistance genes represents a particular challenge for treatment in clinical settings, whereas the spread of pathogens resistant to last resort antibiotics should raise an alarm in the healthcare system worldwide.